A setup for electrochemical corrosion testing at elevated temperature and pressure. (April 2020) - Vallejo Vitaller, Ana; Angst, Ueli M.; Elsener, Bernhard
Highlights: A multi-instrument setup for corrosion testing of metals at high temperature is presented. ZrO2 -based pH electrodes showed hysteresis depending on temperature sweep direction. Data communication interfaces and other unnoticed ground connectors can cause ground loops and introduce measurement errors. Systematic checks are recommended to identify ground loops in complex, multi-instrument measurement setups. Abstract: Laboratory corrosion and scaling testing of metallic materials exposed in high temperature and pressure environments generally involves complex, multi-instrument measurement setups. Here, we present a setup including an autoclave that is instrumented for in-situ electrochemical testing and that contains a ZrO2 -based solid-state pH electrode and devices for temperature control and solution stirring. We show results highlighting the importance of adequate pre-calibration of the pH measurement, due to the hysteresis depending on temperature sweep. Additionally, we illustrate how interfacing the autoclave and the electrochemical cell to measuring and controlling instruments, using different data communication interfaces, can create ground loops. These ground loop interferences can introduce significant errors in the measurement, such as a potential shift of >100 mV. In complex, multi-instrument setups, a complete understanding of ground loops may often be difficult. Thus, we recommend systematic checks to identify the ground loops and we propose measures to avoid them.